Assessing seed priming, sowing date, and mulch film to improve the germination and survival of direct‐sown Miscanthus sinensis in the United Kingdom. Issue 9 (7th June 2018) - Ashman, Chris; Awty‐Carroll, Danny; Mos, Michal; Robson, Paul; Clifton‐Brown, John
Abstract: Direct sowing of Miscanthus seed could lower crop establishment costs, and increase the rate of grower uptake and biomass supply for the emerging bio‐economy. A replicated field trial was conducted at two contrasting UK sites: Aberystwyth (ABR) in mid‐Wales and Blankney (BLK) in Lincolnshire. These sites encompass the west–east meteorological gradient in the United Kingdom where the growing season at ABR is cooler and wetter while BLK is warmer and drier. Primed and unprimed Miscanthus sinensis seeds were sown directly onto the soil surface with and without a clear biodegradable mulch film, at nine dates interspersed from May to October. Average daily mean soil surface temperatures measured over the first 2 months after sowing under the mulch film were higher than control plots (2.7°C ABR and 4.2°C BLK). At both sites, the film covering also affected soil volumetric moisture relative to uncovered control plots (−3% ABR and 8% BLK), demonstrating the negative impact of mulch film when sowing on dry soil. Over nine sowings, seed germination at ABR under film varied between −28% and +18% of germination under control conditions. Seedlings from the first three sowings at both sites under film had sufficient physiological maturity to survive the first winter period. At BLK, mulch film significantly increased tiller count and height in both the first and second years after sowing. At ABR, where temperatures were lower, film covering significantly increased tiller height but not count. Water priming had no significant effect on seed viability or germination in the field tests. Base temperatures for germination of primed and unprimed seeds on a thermal gradient plate were 7.0°C and 5.7°C, respectively, with a ± 1.7°C confidence interval. Based on our results for M. sinensis in the United Kingdom, we recommend the sowing of unprimed seed in May under film and only when the soil is moist. Abstract : Direct sowing of Miscanthus seed could lower costs, benefiting the emerging bio‐economy. A replicated field trial at two different sites in the UK compared primed and unprimed M. sinensis seed sown directly onto soil with and without clear bio‐degradable film, at nine dates from May to October. Results showed the complex interactions between agronomic and meteorological factors and germination and crop establishment.